Food Security and Independence Strategy Through Enhancing the Knowledge and Skills of Group-Based Cattle Farmers in the Cattle Farming Business - Izwar Izwar; Jekki Irawan; Mahrizal Mahrizal (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2024)
Sumber Rezeki Group is a cattle farming group that has been established since 2021, located in Rambong Payong Village, Aceh Jaya. Despite the livestock system being a community-based one, all group members benefit from the income generated from the sale of cattle, which is managed collectively. The purpose of this service is to improve the knowledge and skills of livestock groups in managing the livestock system so that it is effective and well-coordinated. The method of implementing this service is carried out with several stages of implementation, including 1). Socialization, 2). Training, 3). Application of technology, and 4). mentoring. 5) The evaluation and program objectives, which are based on the program evaluation results, are inextricably linked to the indicators of each problem solution. This includes the evaluation of the pre-test and post-test results, as well as the analysis of the observation sheet from the six main indicators, specifically a) fermentation/concentrate formulation.  b). Prevention and control of disease. c). Utilization of livestock manure. d) Independent HPT production using the Silvopastora Agroforestry system; e) Bookkeeping and financial management. e). The marketing system, market analysis, and promotion obtained an average increase in knowledge and skills of members of the source of livelihood group of 80%, in addition to the increase in profits obtained by the partner group from the selling price of Rp. 1,200,000, - increased to Rp. 2,000,000, - per livestock within 7 months.